Multiple endokrine Neoplasie = Multiple endocrine neoplasia - Schaaf, Ludwig; Raue, Friedhelm (Deutsche medizinische Wochenschrift, 2017)
Multiple endocrine neoplasia type 1 and 2 are hereditary cancer syndromes. They are characterized by the occurrence of many benign and malignant tumor types, in MEN1 parathyroid tumors, pituitary tumors, and pancreas tumors, in MEN2 medullary thyroid carcinoma, pheochromocytoma, and parathyroid tumors. The autosomal dominant inherited tumor syndromes are caused by mutations in the MEN1 gene, a tumor suppressor gene, and mutations in the RET gene, an activated oncogene, in MEN2. The clinical expression of the different tumors can vary within and between families, with a good genotype-phenotype correlation in MEN2. Early diagnosis and therapy is possible by using biochemical and imaging screening in the families. Early thyroidectomy in young patients with MEN2 results in a high cure rate of MTC.
Publikationsdatum: 08 September 2017 (online)
Gesehen am 20.09.2018